Cost benefit change of venue of central level of the Comptroller General of the Republic in the city of Bogota (2014)
Since Sandra Morelli Rico took over as General Comptroller of the Republic on August 10, 2010, the company has developed as many changes that have been developed in different administrations to yours. One of the most striking was the change of venue where he worked the Comptroller General of the Republic for 90 years in downtown Bogota towards the sector of Salitre, Grand station in the same city, leading to decisions budgetary basis, including the allocation of funds from the General Budget of the Nation, good reason to determine what is the cost benefit of the change of headquarters of the Comptroller General of the Republic from 2010 to 2014 in the city of Bogotá in the general budget of the Nation ?, concern which seeks to establish the cost benefit of the changes made by the Comptroller General of the Republic of own building located in downtown Bogota to building lease with option to purchase, located in the Saltpeter from the same city sector to which the variations of the public budget of validity 2012 and 2013 as accomplished fact be analyzed, the term 2014 assigned to the Comptroller General of the Republic, being the lifetimes in which it has developed this transfer and allows this information according to a comparison of the cost-benefit analysis from budget analysis mentioned variation years.